Automation in Tree Fruit Production: Principles and Practice 2017
DOI: 10.1079/9781780648507.0043
|View full text |Cite
|
Sign up to set email alerts
|

Light interception and canopy sensing for tree fruit canopy management.

Abstract: This chapter provides a review of the principles, state-of-the-art technology and applications of light interception sensing systems and modelling for use in production agriculture. Case studies are presented where proximally sensed photosynthetically active radiation interception data measured using a mobile platform were used to assist in tree fruit canopy management and estimation of potential yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Furthermore, midday canopy light interception is often defined as the incoming Fractional PAR (fPAR, as a percent) intercepted by a canopy by measuring the PAR both below and above the canopy (McCree, 1966;Lampinen et al, 2012). It indicates actual intercepted PAR (or actual PPFD) that helps growers better understand their orchard productivity and spatial variability (Milne et al, 1992;Rojo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, midday canopy light interception is often defined as the incoming Fractional PAR (fPAR, as a percent) intercepted by a canopy by measuring the PAR both below and above the canopy (McCree, 1966;Lampinen et al, 2012). It indicates actual intercepted PAR (or actual PPFD) that helps growers better understand their orchard productivity and spatial variability (Milne et al, 1992;Rojo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has shown that an optimal orchard can potentially produce 58 lb acre −1 of dried kernel yield for every 1% of canopy fPAR interception, as measured by a mobile lightbar unit (Jin et al, 2020). Rojo et al (2017) also indicated that midday canopy fPAR could be used as a fundamental indicator for estimating the maximum potential yield for almond crop when there are no other stressors present. Although midday fPAR describes the potential yield, only a small portion (e.g., ∼10%) of the trees may reach maximum productivity (Jin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation